2009
DOI: 10.1021/jp8111205
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Conformational Change of meso-Hexakis(pentafluorophenyl) [28]Hexaphyrins(1.1.1.1.1.1) into Möbius Structures

Abstract: At room temperature, meso-hexaaryl-substituted [28]hexaphyrins(1.1.1.1.1.1) in solution exist largely as an equilibrium between planar antiaromatic and distorted Möbius aromatic conformers. As the temperature decreases, the molecular structure changes into the distorted Möbius topology that commonly occurs in [28]hexaphyrins, which gives rise to longer excited singlet and triplet state lifetimes than planar antiaromatic [28]hexaphyrins. Temperature-dependent two-photon absorption measurements of [28]hexaphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 34 publications
11
115
0
3
Order By: Relevance
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
See 1 more Smart Citation
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
“…Consequently, geometry-based indexes of aromaticity [117] become particularly useful in quantitative analysis of such systems, as has been proven for porphyrins [108] and some porphyrin analogues. [103,[118][119][120][121][122][123] Typically used methods are the harmonic oscillator model of aromaticity (HOMA), [103,[120][121][122][123][124] known to give good correlation with magnetic criteria, and the harmonic oscillator stabilization energy method (HOSE) enabling estimation of canonical weights. [118,119,125] …”
Section: Aromaticity Criteriamentioning
confidence: 99%
“…[24] Später wurde gezeigt, dass die Fähigkeit zur Stabilisierung von Möbius-Strukturen eine allgemeine Eigenschaft der Porphyrinoide ist und die Topologie des Makrocyclus zu einem gewissen Maß kontrolliert werden kann. [25,26,103,110,[120][121][122][123][132][133][134] Möbius-Aromatizität kommt zwar relativ selten vor, aber dennoch weit häufiger, als man zunächst erwarten könnte. Weiter unten werden wir auf bestimmte Beispiele zur Möbius-Topologie, die eigentlich schon lange Bestandteil der Porphyrinoid-Literatur sind, aber bis vor kurzem nicht als solche erkannt worden waren, näher eingehen.…”
Section: Möbius-aromatizitätunclassified
“…[236] Diese Merkwürdigkeit konnte zunächst nicht geklärt werden, bis neun Jahre später die Struktur von 41c-H 4 in Lösung durch Tieftemperatur-NMR-Spektroskopie und andere physikalische Methoden erneut analysiert wurde. [121,123] Nach diesen Studien wechselt 41c-H 4 sehr rasch zwischen vier gleichwertigen Möbius-Konformationen (T1), hat aber eine Zwischenstufe der Konformation T0 AD mit konstanter Stellung der invertierten Ringe (Schema 17). Aus diesem Grund weist das dynamisch gemittelte Raumtemperaturspektrum von 41c-H 4 die gleiche Symmetrie auf wie das von 40c-H 2 .…”
Section: Rubyrineunclassified
“…The conformational flexibility, the number and the nature of substituents on the pyrrolic and meso positions, and the metallation of the porphyrins allow them to achieve different topologies with distinct aromaticities, magnetic, and electric properties. 4 In the last five years several Hückel and Möbius topological systems have been prepared through replacement of the solvent and protonation, [5][6][7] temperature control, 8,9 metal coordination, 10 and functional group modifications. 11 As one can see, the synthesis of aromatic systems with Möbius topology has just started and there are still a lot of aspects and applications to be analyzed.…”
Section: Introductionmentioning
confidence: 99%